Exploring Local Wisdom to Develop Educational Cultural Tourism in Sukamandi Masagi Village, Subang - Lala Siti Sahara; Audreylia; Akmal Maulana Purwanto (Politeknik Sahid, 2026)
This study explores the potential for developing educational tourism based on local culture in Sukamandi Village, focusing on traditional arts such as Pencak Silat, Tutunggulan, and regional culinary heritage. A qualitative descriptive method was employed, utilizing observation, in-depth interviews, and documentation. The data collection process was carried out by Lala Siti Sahara, Audreylia Syifanizar E, and Akmal Maulana Purwanto. The findings reveal that these cultural elements possess strong educational value and tourism appeal, yet remain underutilized. Pencak Silat retains authentic “buhun” movements passed down through generations; Tutunggulan holds symbolic significance but is limited to ceremonial events; and local cuisine and bamboo crafts face marketing and generational challenges. The study recommends the development of interactive educational tourism packages featuring hands on training, cultural performances, and culinary experiences. This approach serves both as a tool for cultural preservation and as a driver for local economic growth. The success of such initiatives relies heavily on active community engagement and partnerships with external stakeholders to support training, infrastructure, and sustainable promotion